Small-scale estimation of relative abundance for the coastal spotted dolphins (Stenella attenuata) in Costa Rica: the effect of habitat and seasonality - May-Collado, Laura J. (2012)
The coastal spotted dolphin (Stenella attenuata graffmani) is one of the most common species of dolphin in inshore Pacific waters of Costa Rica. We conducted surveys in protected waters of the Papagayo Gulf, Costa Rica, to determine relative abundance of dolphins in relation to environmental variables. We used Generalized Additive Models to investigate the influence of a particular set of environmental factors and determine inter-annual trends in relative abundance. School sizes ranged from 1 to 50 individuals ( mean 9.95, SD=10.28). The number of dolphins increased linearly with water depth and transparency, and non-linearly with the dissolved oxygen concentration. High variability in the relative abundance occurred during the dry season (January-April). A previous study on this population found that high number of groups are involved in foraging activities during the dry season. Seasonal changes in relative abundance probably are associated with food availability, a variable that we did not measure. Understanding local resident populations may have important implications for conservation and management strategies. Large-scale studies may overlook variables affecting the abundance of local resident populations that may be detected with studies on a smaller scale such as this one.